The Influence of Celebrity Endorser and Price on Consumer Purchase Interest With Brand Image as A Mediation Variable - Gumilang, Dendi Anggi; Ihsan, Luthfi fauziah Nur (Integrated Journal of Business and Economics (IJBE), 2025)
This study examines how price and celebrity endorsements affect consumers' desire to buy, using brand image as a mediating factor. A hundred respondents were surveyed with a non-probability sampling technique combined with a purposive sampling method was used. The data analysis method used is the SEM-PLS model. The research results show that celebrity endorsers significantly influence brand image, price significantly influences brand image, and brand image affects purchasing interest. Celebrity endorsers do not significantly affect purchasing interest directly but through brand image as a mediating variable. Price has a significant effect on purchasing interest both directly and through brand image as a mediating variable. This result shows that brand images play crucial roles in purchase interest, Celebrity endorsers can't just boost the sales of products if the brand image is poor.